New evidence for grain specific C(4) photosynthesis in wheat - Rangan, Parimalan (Sci Rep, 2016)
The C(4) photosynthetic pathway evolved to allow efficient CO(2) capture by plants where effective carbon supply may be limiting as in hot or dry environments, explaining the high growth rates of C(4) plants such as maize. Important crops such as wheat and rice are C(3) plants resulting in efforts to engineer them to use the C(4) pathway. Here we show the presence of a C(4) photosynthetic pathway in the developing wheat grain that is absent in the leaves. Genes specific for C(4) photosynthesis were identified in the wheat genome and found to be preferentially expressed in the photosynthetic pericarp tissue (cross- and tube-cell layers) of the wheat caryopsis. The chloroplasts exhibit dimorphism that corresponds to chloroplasts of mesophyll- and bundle sheath-cells in leaves of classical C(4) plants. Breeding to optimize the relative contributions of C(3) and C(4) photosynthesis may adapt wheat to climate change, contributing to wheat food security.